2004
DOI: 10.1093/alcalc/agh120
|View full text |Cite
|
Sign up to set email alerts
|

Drinking Patterns and Perspectives on Alcohol Policy: Results From Two Ontario Surveys

Abstract: Whether it is intentional or not, government policies that tend to make alcohol more available cater to young, heavy-drinking males who possibly experience problems in connection with their drinking behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
16
1
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 26 publications
5
16
1
1
Order By: Relevance
“…Consistent with previous studies, we found that support for restrictive measures decreased with increased consumption and increased with age, and that it was stronger among women than among men (e.g., Giesbrecht et al, 2005;Greenfield et al, 2007b;van der Sar et al, 2012). The finding indicating that support increased with level of education, is consistent with results from a recent study in Sweden (Holmberg & Weibull, 2013), but deviates from other studies (e.g., van der Sar et al, 2012;Wilkinson et al, 2009).…”
Section: Demographics and Own Drinkingsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with previous studies, we found that support for restrictive measures decreased with increased consumption and increased with age, and that it was stronger among women than among men (e.g., Giesbrecht et al, 2005;Greenfield et al, 2007b;van der Sar et al, 2012). The finding indicating that support increased with level of education, is consistent with results from a recent study in Sweden (Holmberg & Weibull, 2013), but deviates from other studies (e.g., van der Sar et al, 2012;Wilkinson et al, 2009).…”
Section: Demographics and Own Drinkingsupporting
confidence: 91%
“…Accordingly, previous studies have repeatedly shown that support for such restrictions decreases with increasing consumption (e.g., Giesbrecht, Ialomiteanu, & Anglin, 2005;Greenfield et al, 2007b;van der Sar et al, 2012).…”
Section: Possible Predictorsmentioning
confidence: 95%
“…Alcohol consumption seems to impact the opinion on restrictive availability measures of the 16-22-year negatively olds and appears to be the strongest predictor. This is in line with Giesbrecht et al and Giesbrecht and Greenfield [8,10] who found that the drinking pattern predicts views on some alcohol-related policy topics and showed that, in particular, the level of consumption has the greatest explanatory power among an adult population. According to the respondents who never drink alcohol and served as a reference group, drinkers are more negative towards restrictive availability measures than non-users.…”
Section: -18 Yearssupporting
confidence: 86%
“…all drinkers, are affected when these measures are introduced [3]. This assumption is in line with findings of Giesbrecht et al [10] and Giesbrecht and Greenfield [8] who found that the drinking pattern predicts views on some alcohol-related policy topics. This study underlines these conclusions.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation